A pilot examination of the fermentation products, aerobic stability and bacterial community of total mixed ration silage produced in Vietnam. (17th February 2014) - Tran Thi Minh, Tu; Nguyen Huu, Van; Nishino, Naoki
Abstract To evaluate the fermentation characteristics and aerobic stability of total mixed ration (TMR) silage produced in the tropics, rice straw (Rs) and corn stover (Cst) were mixed with molasses (M) and other feeds as TMRs, which were then preserved as silage in Hue, Vietnam. The silages were opened after 4 months, and the microbial counts, fermentation product levels and aerobic stability were determined. The bacterial community was assessed by denaturing gradient gel electrophoresis (DGGE). All the silages were well preserved, with lactic acid serving as the major preservative. However, the lactic acid content was low (5.99 g kg−1 dry matter [DM]) in the Rs‐M silage, while the ethanol content was substantial (37.2 g kg−1DM) in the Cst‐M silage. Heating due to spoilage was observed at 115 and 81 h after silo opening in the Cst‐M and Cst‐TMR silages, respectively, whereas no heating was observed for 7 days after the opening of the Rs‐M and Rs‐TMR silages. Among the 14 bacterial strains identified in the silages by the DGGE analysis, only three were lactic acid bacteria. Lactobacillus brevis and Weissella paramesenteroides were detected in all silages, while W. cibaria was only detected in the Rs‐M and Cst‐M silages. In the aerobically unstable Cst‐TMR silage, bands indicative of Acetobacter pasteurianus, Staphylococcus sp. and Streptomyces sp. were specifically observed. These results indicate that although desirable lactic acid fermentation can be expected in a TMR silage in a tropical environment, aerobic stability is lowered if Cst instead of Rs is used as the ingredient crop. The presence of A. pasteurianus in the air‐tight laboratory silo was unusual, but it could account for the low aerobic stability of the Cst‐TMR silage.